Cost-effectiveness analysis of introducing universal human papillomavirus vaccination of girls aged 11 years into the National Immunization Program in Brazil. (7th May 2015) - Novaes, Hillegonda Maria Dutilh; de Soárez, Patrícia Coelho; Silva, Gulnar Azevedo; Ayres, Andreia; Itria, Alexander; Rama, Cristina Helena; Sartori, Ana Marli Christovam; Clark, Andrew D.; Resch, Stephen
Highlights: We estimate the cost-effectiveness of introducing universal HPV vaccination into the National Immunization Program in Brazil. The HPV vaccination is a very cost-effective strategy, with ICERs below 1 GDP per capita. These estimates will be useful in monitoring the impact of the HPV vaccine introduction. Abstract: Objectives: To evaluate the impact and cost-effectiveness of introducing universal human papillomavirus (HPV) vaccination into the National Immunization Program (NIP) in Brazil. Methods: The Excel-based CERVIVAC decision support model was used to compare two strategies: (1) status quo (with current screening program) and (2) vaccination of a cohort of 11-year-old girls. National parameters for the epidemiology and costs of cervical cancer were estimated in depth. The estimates were based on data from the health information systems of the public health system, the PNAD 2008 national household survey, and relevant scientific literature on Brazil. Costs are expressed in 2008 United States dollars (US$), and a 5% discount rate is applied to both future costs and future health benefits. Results: Introducing the HPV vaccine would reduce the burden of disease. The model estimated there would be 229 deaths avoided and 6677 disability-adjusted life years (DALYs) averted in the vaccinated cohort. The incremental cost-effectiveness ratios (ICERs) per DALY averted from the perspectives of the government (US$ 7663), health system (US$ 7412), and society (US$ 7298) would be considered cost-effective, according to the parameters adopted by the World Health Organization. In the sensitivity analysis, the ICERs were most sensitive to variations in discount rate, disease burden, vaccine efficacy, and proportion of cervical cancer caused by types 16 and 18. However, universal HPV vaccination remained a cost-effective strategy in most variations of the key estimates. Conclusions: Vaccine introduction could contribute additional benefits in controlling cervical cancer, but it requires large investments by the NIP. Among the essential conditions for attaining the expected favorable results are immunization program sustainability, equity in a population perspective, improvement of the screening program, and development of a surveillance system.